Socio-Cultural Factors Associated with Utilization of Routine Immunization Services by Childbearing Mothers in Gombe State - Usman, Bilyaminu A.; Nwagu, Evelyn N. (International Journal of Human Kinetics, Health and Education, 2022)
This study investigated the socio-cultural factors associated with utilization of Routine Immunization Services (RIS) among child-bearing mothers in Gombe State. The study adopted descriptive cross-sectional survey research design. The population for the study comprised all 517,853 child-bearing mothers (CBMs) attending general hospitals and primary health facilities in Gombe State. The sample size for the study was 400 child-bearing mothers. The instrument for data collection was a questionnaire titled ‘Socio-Cultural Factors Associated with Utilization of Routine Immunization Services (RIS) (SOFAURIS)’. The instrument was validated by five experts. The reliability index of the instrument was 0.80. The research questions were answered using frequencies, percentages and Phi correlation coefficient, while, the null hypotheses were tested at 0.05 significance level using Chi-square statistic. The findings showed that the proportion of the mothers that utilized RISs (68%) in Gombe State was higher than the proportion that did not (32%). Tangale mothers (71.2%) utilized RIS most among the ethnic groups, Christian mothers (77.3%) utilized RIS most among the religious groups in the State with a significant association (φ = 0.154; χ2 = 9.489; S = 0.009) between religion and utilization of RISs in Gombe State. The authors recommended among others that government, traditional and religious leaders and NGOs should sensitize child bearing mothers to immunize their children in order to increase the proportion of mothers that utilize RIS.